Cultural Presuppositions and Misreadings - Ping, Ke (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractOf the many factors that may lead to misreadings in translation, cultural presuppositions merit special attention from translators because they can substantially and systematically affect their interpretation of facts and events in the source text without their even knowing it. This paper attempts to pinpoint the relationship between cultural presuppositions and translational misreadings. The author considers major elements in the four subsystems of culture and examines how these elements help breed presuppositions that inadvertently affect the translator's decoding of the original message.